Optimizing Consultation Services Through Spiritual Guidance: Religious Counselors in Overcoming Religious Problems in Kudus Communities - Bastomi, Hasan; Mundakir, Akhmad (Konseling Edukasi : Journal of Guidance and Counseling, 2024)
Optimizing Consultation Services Through Spiritual Guidance: Religious Counselors in Overcoming Religious Problems in Kudus Communities. This research aims to reveal religious counselors in overcoming religious problems in the Kudus community through consultation services. This research on religious instructors in overcoming religious problems in the Kudus community through consultation services was carried out using a qualitative approach with the type of field research with data collection techniques using Interview, Observation and Documentation techniques. The research subjects or informants in this research were religious instructors and the Kudus community. The results of the research show that the Optimization of Kudus Regency Religious Extension Consultation Services in the Development of the Islamic Community is carried out in the form of spiritual counseling to the assisted communities to help them overcome spiritual crises, moral conflicts, or questions about religious beliefs in the Kudus community. For further research, it is recommended to explore more deeply the various factors that influence the effectiveness of spiritual guidance, such as the counselor's educational background, the approach used, and institutional support.Keywords: Optimization, Consultation Services, Religious Counselors, Religious Problems, Kudus Society